1974
DOI: 10.1161/01.cir.50.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of Echocardiographic Diagnosis of Pericardial Effusion

Abstract: In order to evaluate the reliability and sensitivity of echocardiograms for detecting and quantitating pericardial effusion, 41 patients had echocardiograms on the day prior to cardiac operation. A fluid trap was used to aspirate the pericardium at operation. Thirty-nine of 41 patients had echocardiograms of diagnostic quality. In 25 patients, the echocardiogram was negative for pericardial effusion, with 0-16 ml identified at operation. In 13 patients, the echocardiogram was positive for pericardial effusion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0
9

Year Published

1978
1978
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(87 citation statements)
references
References 23 publications
1
77
0
9
Order By: Relevance
“…The three observers were in agreement about the interpretation of the two-dimensional studies in all 21 cases in which doubts had been raised by the M mode echocardiogram or in which a pattern of effusion was persistent on the latter. Two-dimensional recordings confirmed that the M mode echo-free space corresponded to PE in 1 1, whereas in the remaining 10 this space could have been related to other adjacent structures.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The three observers were in agreement about the interpretation of the two-dimensional studies in all 21 cases in which doubts had been raised by the M mode echocardiogram or in which a pattern of effusion was persistent on the latter. Two-dimensional recordings confirmed that the M mode echo-free space corresponded to PE in 1 1, whereas in the remaining 10 this space could have been related to other adjacent structures.…”
Section: Resultsmentioning
confidence: 69%
“…(5) X-ray changes. For all patients at least three x-ray chest films were available, two of which were obtained within the 4 first days after admission and the third of which was obtained on day 10. All were examined looking for changes in heart size, findings suggesting heart failure, and signs of pleural effusion.…”
Section: Methodsmentioning
confidence: 99%
“…Early and late diastolic, and peak systolic mitral annular velocities were recorded. Pericardial effusion was defined according to the method of Horowitz et al 15 An epicardial-pericardial separation that persisted throughout the cardiac cycle (D pattern) was considered diagnostic of pericardial effusion.…”
Section: Echocardiographymentioning
confidence: 99%
“…Echocardiograms were not obtained routinely, but rather, as clinically indicated. The echocardiographic diagnosis of pericardial effusion was made using the criteria proposed by Horowitz et al 9 The usual uncomplicated hospital stay was 10-14 days. Monthly follow-up visits for all 1122 patients (87%) who lived in the area began 1 month after discharge during the first postoperative year and every 6 months thereafter.…”
mentioning
confidence: 99%